Analisis de procesos licitatorios y asignacion de riesgos en asociaciones publico privadas: caso autopista conexión norte (2020)
Analysis of bidding processes and risks distribution in public-private partnerships for the-Conexión Norte highway case. A comparison is made between the bidding processes and the risks distribution in the contract with the theory proposed by Yescombe.